2022
DOI: 10.4254/wjh.v14.i1.295
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation for autoimmune hepatitis: A need for further investigation

Abstract: Autoimmune hepatitis is a chronic liver disease harboring an autoimmune basis and progressive character. Despite still obscurity in etiology and pathogenesis, some evidence supports the importance of sustaining the immune system. Vitamin D is a lipo-soluble vitamin, which has been identified as decreased in our body. It is often due to the daily habit change and decrease of individual sun exposure due to the increase of the ultraviolet-induced potential melanocytic transformation. Here, we emphasize the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Noticeably, several other supplements have been reported for AIH treatment previously. For example, Vitamin D supplementation may alleviate the interface hepatitis in AIH patients, and influence advanced liver fibrosis, as well as the need for liver transplantation [ 16 ]. It also has been shown that zinc supplementation could safely and efficiently improve mental impairment caused by continuous treatment with corticosteroids in patients with AIH [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, several other supplements have been reported for AIH treatment previously. For example, Vitamin D supplementation may alleviate the interface hepatitis in AIH patients, and influence advanced liver fibrosis, as well as the need for liver transplantation [ 16 ]. It also has been shown that zinc supplementation could safely and efficiently improve mental impairment caused by continuous treatment with corticosteroids in patients with AIH [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence of a link between low vitamin D levels and autoimmunity. In autoimmune hepatitis (AIH), a deficiency of 25(OH)D3 (less than 10 ng/mL) has been associated with severe inflammatory activity of the liver or interface hepatitis, progressive liver fibrosis, and treatment failure [ 100 ].…”
Section: Possible Mechanisms Of the Association Between Vitamin D–vdr...mentioning
confidence: 99%
“…Vitamin D supplementation in patients with AIH has been advocated [ 100 ] because it has been demonstrated that circulating 25-hydroxyvitamin D levels are low in the majority of patients with AIH and that they have an increased nonresponse rate to steroids compared with healthy individuals [ 103 ]. Vitamin D supplementation has been shown to reduce inflammation and limit liver injury in patients with AIH, acting mainly as an antioxidant [ 104 ].…”
Section: Possible Mechanisms Of the Association Between Vitamin D–vdr...mentioning
confidence: 99%
“…Still, it is presumed to have an infectious trigger behind the initialization of the inflammatory process of the liver. In some cases, the cause is a virus, which stimulates an inflammatory response, and vitamin D harboring randomized clinical trials has been promising in addition to immunosuppressive therapy ( Domerecka et al, 2021 ; Sergi, 2022a ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that molecular mimicry may be the basis of several autoimmune reactions in the human body. Due to its molecular mimicry, the antibodies against the SARS-CoV-2 spike protein may disclose a high affinity for several human proteins and trigger autoimmune phenomena ( Sergi, 2022a ).…”
Section: Introductionmentioning
confidence: 99%